DETERMINAN KINERJA PENYELENGGARAAN PEMERINTAH DAERAH (STUDI EMPIRIS PADA PEMERINTAH KABUPATEN/KOTA DI INDONESIA) - Magister Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Sebelas Maret Surakarta, Dwi Hari Saktia (MAJALAH ILMIAH GEMA, 2014)
This paper discusses about performance of local governments in Indonesia. Performance is an issue that is currently rampant discussed because of performance related to accountability or responsibility in managing state finances government mandated by the society to them. This study aims to examine the effect of financial investigation from Supreme Audit Institution in Indonesia - BPK RI (audit findings of internal control weakness, audit findings of noncompliance with regulations, and audit opinion) with the local governmentâs performance in Indonesia.This study uses multiple regression method to 315 districts/municipalities as a sample selected by purposive sampling method. This study provides evidence that the result of investigation by BPK about audit findings of internal control weakness and audit findings of noncompliance with regulations have significant negative effect on local governmentâs performance, and audit opinion have significant positive effect on local governmentâs performance. That means the implementation of investigating is very influential the local governmentâs performance in Indonesia. Keywords: internal control weakness, audit findings of noncompliance with regulations, audit opinion, BPK, local governmentâs performance in Indonesia.